Are you what you consume? Impact of food, soft drinks, and coffee on cognitive and non-cognitive test scores - Thomas Pave Sohnesen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Cognitive and non-cognitive tests are key factors in many aspects of economics, especially within labour market analysis. Non-cognitive tests and personality traits are increasingly used, as these are found to be as critical as cognitive abilities for labour market outcomes, while they might be more malleable through life. Intake of caffeine and sugar immediately prior testing is also known to impact cognitive test scores, while almost nothing is known about any similar impact on personality test scores. This work shows, as a first, a significant impact from coffee on the personality trait locus of control. The impact from coffee on locus of control is so large that it significantly alters the results of an analysis of locus of control's importance for labour market behaviour. Consumption of food, soft drinks, or coffee is found to have no impact on verbal, numerical, and Raven's Progressive Matrices tests. The study is based on a large sample of university students in Mozambique.
Keywords: J24; I2; 330; cognitive test; non-cognitive test; measurement error; caffeine; glucose; labour market